Routing Wavelength Assignment: New Snake-One Heuristic for Wdm Networks with Dynamic Traffic [Enrutamiento y Asignación de Longitud de Onda: Nueva Heurísticasnake-One Para Redes Wdm Bajo Tráfico Dinámico] - Rodriguez-Garcia, A; Rodriguez-Garcia, A (Universidad de Tarapaca, 2016)
In this paper is shown the simulation results of a new heuristic, called snake-one. The simulation was performed in the National Science Foundation NETwork (NSFNET-USA) under dynamic traffic and compared with other heuristics such as Simulated Annealing, Genetic Algorithms and Tabu Search previously released, using the Blocking Probability indicator and Network Utilization. Comparing these heuristics, we can observe the improvement, of the blocking up to 130 Erlangs. Nevertheless, this results mean an increased and sustained use of the network. This behavior determines a partially good result, which determines the study of a modification of the Snake-one algorithm to improve both indicators. © 2016, Universidad de Tarapaca. All rights reserved.